The Effectiveness of Preparation for Marriage Education with PREP in Iran. Issue 4 (19th May 2021) - Fathi, Elham; Daneshpour, Manijeh; Hatami Varzaneh, Abolfazl
Abstract: Premarital education can benefit couples from many socioeconomic levels. This study aimed to validate the PREP questionnaire and then explore the effectiveness of PREP education for Iranian couples. This study has been done in two phases. In the first phase, the PREP questionnaire was validated. In the second phase, quasi-experimental research was conducted in a pretest-post-test control group design to examine the effectiveness of the PREP education for 15 participants in the experimental group and 15 participants in the control group. The results of factor analysis in the first phase of the study revealed that the PREP questionnaire consists of four factors of Friendship and Emotional Safety; Communication Danger Signs; Social Integration, and Communication Skills. In the second phase of PREP education, there was a significant difference between the experimental and control groups in the post-test on all four factors. Also, there was a significant difference between the experimental and control group on all factors except Social Integration. We can conclude that by utilizing PREP, the researchers found that interpersonal relationships are highly valued for participants and utilizing PREP and other educational programs can successfully help Iranian couples navigate through the complexity of relational dynamics with more knowledge and skills.